Evaluation of Hibiscus esculentus Linn. on the Mechanical and Disintegration Properties of Paracetamol Tablets (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The effects of mucilage obtained from the ripe fruits of Hibiscus esculentus Linn. (Malvaceae) on the mechanical and disintegration properties of paracetamol tablets were investigated against gum acacia as a standard binding agent. The effects of the nature and concentration of the mucilage binder and the relative density of the tablet on the tensile strength, brittle fracture index and disintegration time of the tablets were investigated. Relative density, concentration and nature of binder had the greatest effects on tensile strength, brittle fracture index and disintegration time, respectively. Increasing, the concentration of mucilage from 2.5 % to 10.0 % w/w, and increasing relative density of the tablet from 0.70 to 0.80 led to an increase in tensile strength and disintegration time, but a decrease in brittle fracture index. Tablets formulated with H. esculentus mucilage had lower tensile strength and disintegration time values than those containing gum acacia, and exhibited less lamination and capping. The nature and concentration of binder had the highest interaction among the factors studied. In conclusion, Hibiscus esculentus mucilage could be useful as an alternative binding agent to gum acacia, especially where faster disintegration is required and lamination and capping are of concern.
Keywords: Hibiscus esculentus; mucilage; binding agent; paracetamol; tensile strength; brittle fracture index; disintegration time